PENGARUH DAYA LISTRIK MEDIA TERHADAP KERAGAAN BIBIT TANAMAN VIOLA (Viola cornuta L.) - Alfa Sada Saputra; Suprihati Suprihati (Agric, 2018)
Electrical conductivity (EC) of nursery medium will affect germination and growth of viola (Viola cornuta L.) seedling. The purpose of this study was to determine the influence of various ECs of growing medium on germination and growth of viola seedling. Research was carried out in December 2016 - January 2017 in nursery room of PT. Selektani Horticulture, Ngablak, Magelang. There were 9 EC treatments repeated 3 times therefore 27 units of experiment were tested. The observed parameters includeds germination rate (DB), and speed (KCT), plant height, number of leaves, shoot dry weight (BKBA) and root dry weight (BKA). Data were analyzed using regression and correlation tests. This study showed that there was a linear relationship between EC and DB as well as between EC and KCT. This is indicated by the following equations y = -20.771x + 99 504 (R2 = 0.9653, n = 27, y = germination (%), x = EC (dS / m) 0 HSS) and y = -5.1109x + 21.6 (R2= 0.8765, n=27, y= KCT (%KN/24hours). The critical EC needed to reach germination rate of higher than 80% was 0.94 dS/m. The correlations between DB and ec as well as KCT and EC were significant: respectively -0.98251 and -0.93621 (n = 27). The Relationships between EC and plant height, number of leaves, BKBA as well as BKA were quadratic. The optimum EC needed for seedling growth was 2.44-2.60 dS/m. The correlation betweenplant height and number of leaves was very strong as showed by the value at 0.9212. The correlation between BKBA and BKA was strong and this was indicated by the value of 0.7561.